Retracted: The Split Common Fixed Point Problem for Quasi-Total Asymptotically Nonexpansive Uniformly Lipschitzian Mappings. (15th May 2012) - Na Na, Jing Jing; Wang Wang, Lin Lin; Ma Ma, Zhaoli Zhaoli
Abstract : This article has been retracted as it is found to contain a substantial amount of material, without referencing, from the paper "The Split Common Fixed Point Problem for Total Asymptotically Strictly Pseudocontractive Mappings, " Shih-sen Chang, Lin Wang, Yong Kun Tang and Li Yang, Journal of Applied Mathematics, vol. 2012, Article ID 385638, 13 pages, 2012. doi:10.1155/2012/385638 [1].